Proceedings of 2005 IEEE Conference on Control Applications, 2005. CCA 2005.
DOI: 10.1109/cca.2005.1507091
|View full text |Cite
|
Sign up to set email alerts
|

Robotic suturing forces in the presence of haptic feedback and sensory substitution

Abstract: -There has been some interest in recent years on how information about interactions happening between surgical instruments and tissue during robot-assisted surgery could improve the efficiency and reliability of a surgical task. In this paper, it is hypothesized that various modes of sensory feedback have the potential to enhance performance in robotassisted surgery in terms of the amount of applied forces. User performance during telemanipulated suturing is compared for cases where force feedback is replaced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Also, haptics can provide a means of introducing realism in simulators for needle insertion training. Although teleoperated procedures can benefit from the addition of force feedback [99,100] (especially when the quality of imaging is not good), it is known that real-time imaging feedback of sufficiently good quality is a more effective aid than haptic feedback alone [27].…”
Section: Robotics and Controlmentioning
confidence: 99%
“…Also, haptics can provide a means of introducing realism in simulators for needle insertion training. Although teleoperated procedures can benefit from the addition of force feedback [99,100] (especially when the quality of imaging is not good), it is known that real-time imaging feedback of sufficiently good quality is a more effective aid than haptic feedback alone [27].…”
Section: Robotics and Controlmentioning
confidence: 99%
“…Previous works [20] showed that the 4-DoF continuum snake arm can transmit axial rotation provided that exact synchronous actuation of all secondary backbones is ensured by proper compensation for model imperfections. However when the parallelogram mechanism opens and deforms the flexible stem, interaction forces will severely affect the torque transmission and the 50 mNm required [24] for suturing may be unavailable. To simplify the design and control of the IREP arms, an independent single DoF wrist located at the distal end of each IREP arm was chosen to meet the functional requirements, including dexterity, actuation speed and payload ability.…”
Section: Wrist Designmentioning
confidence: 99%
“…As it was reported by Bethea et al [99], while working with minimally invasive robotic systems with no haptic feedback, even experienced surgeons often tear apart sutures and damage delicate tissues. In [100], Tavakoli et al demonstrated that force interaction information can assist the user in exerting lower amount of forces on tissue during telemanipulated suturing maneuvers. In another quantitative study by Wagner et al [101], subjects used a telerobotic system to perform a blunt dissection task and expose an artery in a synthetic model while viewing the operative site with a video laparoscope.…”
Section: A General Minimally Invasive Surgerymentioning
confidence: 99%